EFFECTIVE WAREHOUSE MANAGEMENT USING LEAN CONCEPTS AND ITS EFFECTS ON PAKISTAN’S FMCG INDUSTRY - MUHAMMAD RAFAY SHAIKH; DR. MUHAMMAD ASIM; SALMAN MANZOOR (CenRaPS Journal of Social Sciences, 2020)
Warehousing plays an important role in integrating the supply chain of the industry. But given the volatility and dynamic nature of supply chain management as a field, the factors that need to be considered when implementing lean in the warehousing that not every warehouse structure is the same. While implementing other external factors and the concerns of the people working the warehousing needs to be considered. Because the purpose is the same that effective and efficient warehouse, with less cost and more profit. In addition to this, the study will describe and the theory of core competencies on parallel practices and how these competencies are used in implementing the lean methodology in the warehouse. A survey was carried out through questionnaires to determine which competencies are best suited to choosing a lean in the warehouse. Hypothetically, the findings showed that in making warehouse effective all three independent factors have their own significance over the provided two dependent factors. Concluding, the study will act as a touchstone in understanding the lean management practices on shorter yet connected enterprises in small to large scale industries.